Assessment of the nutritional status of the elderly and its correlates - Rashmi Agarwalla; Anku Moni Saikia; Rupali Baruah (Wolters Kluwer Medknow Publications, 2015)
Background: The percentage of elderly is growing rapidly and malnutrition is not uncommon in the elderly. Objectives: The present study was carried out to assess the nutritional status of the elderly using the Mini Nutritional Assessment (MNA) tool, and to study the various epidemiological factors influencing their nutritional status. Materials and Methods: This cross-sectional study was done from July 2012 to August 2013 in Boko-Bongaon Block, Kamrup District, Assam, India. The elderly, those over 60 years of age, who met the inclusion criteria participated in the study. A total of 30 clusters were selected and 12 elderly from each cluster were taken to achieve the desired sample size of 360. Nutritional status was assessed by the MNA tool and a 24-h dietary recall method. Results: Out of the total of 360 elderly persons, 15% were found to be malnourished and 55% were at risk of malnutrition. The association between nutritional status and older age group, female gender, dependent functional status, dependent financial status and inadequate calorie intake was found to be significant. Conclusion: The present findings reveal that malnutrition is not an uncommon problem in the elderly, and further studies are needed in this regard.